Population genetics of horticultural crops aided by multi-omics technology and its implications for ornamental plants - Bixuan Cheng; Wenting Du; Peter M. Bourke; Chao Yu (Ornamental Plant Research)
Population genetic studies have long been an essential part of dissecting important traits of crops. The advent of genomic resources has significantly enhanced the efficiency of genetic mapping studies. Concurrently, the integration of multi-omics approaches affords a comprehensive perspective of plant systems, enabling researchers to investigate the correlations between genetic variations and horticultural traits across multiple dimensions. This review summarized studies combining forward genetics with multi-omics resources to analyze the genetic basis of important traits in horticultural crops. The strategies for the effective application of these integrated approaches in the genetic dissection of ornamental plant populations was discussed. The challenges in processing large dataset were acknowledged and promising prospects of artiﬁcial intelligence (AI) when addressing such issues were outlined. The review aims to provide guidance for population genetic research of horticultural crops and ornamental plants in the multi-omics era.